The affixal word-building models of the banking terms (on the material of the substantive Anglicism) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The specifics of the manifestation of the affixal word-building models bank term- anglicisms is analyzed. The productive suffixal and prefixal models of the banking substantives are differentiated; the semantics of the formant is defined. The nature forming bases is installed. The status and purpose pre- and postpositive affixoids in the term’s morphemic structure are commented.
Keywords: affixation; banking term; substantive anglicism; word-building model